INCREASING THE SPIRITUAL CAPACITY OF YOUTH AND EDUCATING THEM IN A SPIRIT OF PATRIOTISM (Scientific journal of the Fergana State University, 2025)
This article analyzes the fact that today in our country, processes of modernization and renewal of all sectors are being consistently carried out, and that the main goal of innovation processes, along with the development of society, is to ensure a stable life, freedom, peace, and a fulfilling life for people, and that it is important that the upbringing and education of the younger generation be based on both national traditions and values, and advanced international experience.